Regional Dynamics of Insurances in Romania - Dan Constantinescu; Constantin Rotaru; Marius-Nicolae Jula (European Regional Science Association (ERSA), 2010)
In the paper we analyze the economic, social, cultural, institutional and political factors that determine regional demand for services like "insurance". As economic factors, we analyze the impact of non-governmental credit over the insurance market. Development of an econometric model is based not only on the actual loan methodology (involving the securities, life insurance for applicants and guarantors), but also on direct connections from the range of credit risk insurance products. On the other hand, non-government credit growth, by enhancing repayment commitments, leads to a reduction in financial resources that can be used, for example, to voluntary/optional insurances, not directly linked with loan process. Last but not least, above-mentioned interferences put footprint on specific partnerships, such as – for example – bancassurance. The residues from the regression equation specific to each region can be explained by social and cultural characteristics. Based on these results, we considered two scenarios for the regional evolution of Romanian insurance market, first determined by the significant factors of this process (GDP/ capita, monthly nominal average wage/capita, population, size of distribution network) as they were outlined in a previous study, the second taking into account the new predictions of non-governmental loan in terms of economic and financial crisis.
Keywords: G21; G22; R12; 330; insurance (life/general and on types); loans (on categories); regional distribution; disparities; correlations; concentration; panel model; forecast